Guide :

prove associative law

prove cummutative law

Research, Knowledge and Information :

Proof of The Associative Law and The Commutative Law.

The associative law of multiplication for three positive integers \$a,b\$ and \$c\$ can be proved\$^1\$ from the Commutative Law and the property of "Number of things" easily.

Associative Law of Set for Union, Intersection - Definition ...

Associative law of set theory used for intersection and union of three different sets.

Commutative, Associative and Distributive Laws - Math Is Fun

Commutative, Associative and Distributive Laws. Wow! ... Distributive Law. The "Distributive Law" is the BEST one of all, but needs careful attention.

Associative property - Wikipedia

In mathematics, the associative property ... Formally, a binary operation ∗ on a set S is called associative if it satisfies the associative law:

Prove an Associative Law (set theory) | Physics Forums - The ...

Physics Forums - The Fusion of Science and Community

Math Forum - Ask Dr. Math

How can you prove or derive the commutative, associative, and distributive properties of numbers?

Definition of Associative Law - Math is Fun

The "Associative Laws" say that it doesn't matter how we group the numbers (i.e. which we calculate first) ..... when we add... or when we multiply.

Distributive Law Property of Set Theory Proof - Definition

Distributive Law of Set Theory Proof - Definition. Distributive Law states that, the sum and product remain the same value even when the order of the elements is altered.

Use the associative law of multiplication to write an equivalent expression. 5[x(2 + y)]

5[x(2 + y)] = (5x)(2 + y) Note that we are to use associativity of multiplication and nothing else. Thus, do not distribute 5x into (2 + y).

Prove that (AnB)' = A'uB'

Examples on De Morgan’s law: 1. If U = {j, k, l, m, n}, X = {j, k, m} and Y = {k, m, n}. Proof of De Morgan's law: (X ∩ Y)' = X' U Y'. Solution: We know, U = {j, k, l, m, n} X = {j, k, m} Y = {k, m, n} (X ∩ Y) = {j, k, m} ∩ {k, m, n} = {k, m} Therefore, (X ∩ Y)' = {j, l, n} ……………….. (i) Again, X = {j, k, m} so, X' = {l, n} and Y = {k, m, n} so, Y' = {j, l} X' ∪ Y' = {l, n} ∪ {j, l} Therefore, X' ∪ Y' = {j, l, n} ……………….. (ii) Combining (i)and (ii) we get; (X ∩ Y)' = X' U Y'. Proved 2. Let U = {1, 2, 3, 4, 5, 6, 7, 8}, P = {4, 5, 6} and Q = {5, 6, 8}. Show that (P ∪ Q)' = P' ∩ Q'. Solution: We know, U = {1, 2, 3, 4, 5, 6, 7, 8} P = {4, 5, 6} Q = {5, 6, 8} P ∪ Q = {4, 5, 6} ∪ {5, 6, 8} = {4, 5, 6, 8} Therefore, (P ∪ Q)' = {1, 2, 3, 7} ……………….. (i) Now P = {4, 5, 6} so, P' = {1, 2, 3, 7, 8} and Q = {5, 6, 8} so, Q' = {1, 2, 3, 4, 7} P' ∩ Q' = {1, 2, 3, 7, 8} ∩ {1, 2, 3, 4, 7} Therefore, P' ∩ Q' = {1, 2, 3, 7} ……………….. (ii) Combining (i)and (ii) we get; (P ∪ Q)' = P' ∩ Q'. Proved

Prove the third law of exponents

The meaning of x^(m/n) I guess is the third law. x^(1/n) means the n-th root of x. If y=x^(1/n) then y^n=x. So y is the n-th root of x. This is the same as x^(1/n*n)=x^1=x. y^m=(x^(1/n))^m=x^(1/n*m)=x^(m/n). This is the same as (the n-th root of x) raised to the power m; or it is the n-th root of (x raised to the power m). These mean the same thing. Example: 64^(1/6)=2 so 2^6=64; 64^(2/3)=2^(6*2/3)=2^4=16. 64^(1/3) is the cube root of 64=4. 64^(2/3) is (cube root of 64) squared=4^2=4*4=16. And 64^2=(2^6)^2=2^12, so 64^(2/3)=(64^2)^(1/3)=(2^(6*2))^(1/3)=(2^12)^(1/3)=2^(12/3)=2^4=2*2*2*2=16.

Commutative laws

in a triangle abc, if ab is the greatest side, then prove that angle c > 60

yukan yuze law av sines: (sine angel) / (leng av side kros from angel)=konst so...longest side kros from biggest angel...same for smallest & (leng side 1) / (leng side 2)=(sine angel 1) / (sine angel 2)